LIFETIME LAMB PRODUCTION OF NILAGIRI EWES - IYUE, M; KUMAR, R ANIL; VENKATARAMANAN, R; SREEKUMAR, C (The Indian Journal of Animal Reproduction, 2022)
The reproductive rate and lifetime productivity of ewes of Nilagiri sheep was assessed as a trait of ewe andexpressed in terms of number of lambs produced (TLB), number of lambs weaned (TLW) and total weight weaned(TWW). Data from 2146 lambing records of Nilagiri ewes born during the period from 1978 to 2001 were analyzed.The mean number of lambs born per ewe during their lifetime varied from 3.69 ± 0.14 to 5.08 ± 0.36 for the differentperiods with an overall mean of 4.59 ± 0.12. The differences in total lambs born between the periods is significant(P
Keywords: Nilagiri sheep; Lifetime ewe productivity traits; number of lambs produced; number of lambs weaned; total weight weaned